Nursing and Society - Fernández-Martínez, Elena; Gomes, Lisa Alves; Liébana-Presa, Cristina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The year 2020 is considered by the World Health Organization to be the International Year of the Nurse and Midwife. This book supports the visibility of the contribution of nurses to society. We have included 30 articles on high-quality original research or reviews that provide solid new discoveries that expand current knowledge.